2019
DOI: 10.1039/c8cc08985j
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric construction of dihydrobenzofuran-2,5-dione derivatives via desymmetrization of p-quinols with azlactones

Abstract: 3-Amino-benzofuran-2,5-diones containing a chiral amino acid residue were achieved through BG-1·HBPh4 catalyzed enantioselective Michael addition/lactonization cascade reaction of p-quinols with azlactones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For instance, a direct CPA-catalyzed Friedel-Crafts alkylation of indoles with para-quinols (24) was explored by Carreño and coworkers [44]. Later in 2019, the Liu group used azlactones as reactants to discover a chiral bisguanidinium hemisalt-catalyzed tandem Michael addition/lactonization reaction, providing an entry to dihydrobenzofuran-2,5diones (26) with concomitant establishment of three contiguous stereocenters [45]. Meanwhile, the application of hemiaminals as bifunctional substrates could lead to the assembly of N,O-ketal motifs (27), as demonstrated by Wang [46].…”
Section: Desymmetrization Of Prochiral Enonesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a direct CPA-catalyzed Friedel-Crafts alkylation of indoles with para-quinols (24) was explored by Carreño and coworkers [44]. Later in 2019, the Liu group used azlactones as reactants to discover a chiral bisguanidinium hemisalt-catalyzed tandem Michael addition/lactonization reaction, providing an entry to dihydrobenzofuran-2,5diones (26) with concomitant establishment of three contiguous stereocenters [45]. Meanwhile, the application of hemiaminals as bifunctional substrates could lead to the assembly of N,O-ketal motifs (27), as demonstrated by Wang [46].…”
Section: Desymmetrization Of Prochiral Enonesmentioning
confidence: 99%
“…A combination of experimental and theoretical studies indicated that a supramolecular catalytic pathway was speculatively involved. Two years later, an impressive procedure for thiourea-catalyzed asymmetric cycloetherification of in situ-generated gem-diols (45-A) from ketones (45) was accomplished by Matsubara (Figure 4D) [64]. Notably, the presence of H 2 O here could not only promote the generation of gem-diols but also stabilize the hemiketal products (46) from further degradation.…”
Section: Desymmetrization Of Prochiral Diols and Bisphenolsmentioning
confidence: 99%
“…The presence of three contiguous chiral centers in the compound was supposed to serve as a good building block to synthesize various natural products like sorbicillactone A and B (Scheme 36). [99] …”
Section: Asymmetric Reactionsmentioning
confidence: 99%
“…The presence of three contiguous chiral centers in the compound was supposed to serve as a good building block to synthesize various natural products like sorbicillactone A and B (Scheme 36). [99] The first Lewis acid, FeCl 3 ⋅ 6H 2 O catalyzed Friedel-Crafts alkylation of indole 332 was reported with good selectivities by using para-quinol 331 as electrophiles to compound 334. Reaction underwent a 1,4-addition reaction in a high p-facial diastereoselective manner.…”
Section: Asymmetric Reactionsmentioning
confidence: 99%
“…In 2019, Liu's group described a straightforward method for accessing 3‐amino‐benzofuran‐2,5‐diones ( 145 ) through a 1,4‐conjugate addition/lactonization cascade reaction between para ‐quinols ( 142 ) and azlactones ( 143 ), catalyzed by a chiral bisguanidinium hemisalt ( 144 ) (Scheme A) . The desired products containing three contiguous stereogenic centers were obtained in low to excellent yields (29–94 %) and with high diastereomeric ratio (> 19:1 d .…”
Section: Conjugate Additions and Other Enolate‐mediated Reactionsmentioning
confidence: 99%